Antibody-mediated targeting of the transferrin receptor in cancer cells - Rosendo Luria-Pérez; Gustavo Helguera; José A. Rodríguez (Permanyer, 2016)
Iron is essential for cell growth and is imported into cells in part through the action of transferrin (Tf), a protein that binds its receptor (TfR1 or CD71) on the surface of a cell, and then releases iron into endosomes. TfR1 is a single pass type-II transmembrane protein expressed at basal levels in most tissues. High expression of TfR1 is typically associated with rapidly proliferating cells, including various types of cancer. TfR1 is targeted by experimental therapeutics for several reasons: its cell surface accessibility, constitutive endocytosis into cells, essential role in cell growth and proliferation, and its overexpression by cancer cells. Among the therapeutic agents used to target TfR1, antibodies stand out due to their remarkable specificity and affinity. Clinical trials are being conducted to evaluate the safety and efficacy of agents targeting TfR1 in cancer patients with promising results. These observations suggest that therapies targeting TfR1 as direct therapeutics or delivery conduits remain an attractive alternative for the treatment of cancers that overexpress the receptor.